High pressure assisted extraction of proteins from wet biomass of Arthrospira platensis (spirulina) – A kinetic approach. (October 2022) - Giannoglou, Marianna; Andreou, Varvara; Thanou, Ioanna; Markou, Giorgos; Katsaros, George
Abstract: The application of high-pressure technology (100–600 MPa, 20 °C for up to 20 min) for cell disruption and consequent extraction of proteins -including C-phycocyanin- from the cyanobacteria Arthrospira platensis (spirulina), was investigated. Wet spirulina biomass was suspended in three different aqueous systems (deionized water, phosphate buffer, 10% sodium chloride solution). During a-24 h post processing storage period at 20 °C, the concentration of total soluble proteins and C-phycocyanin content and purity were measured. Color-spectrum and chroma analyses were also performed. The use of deionized water and phosphate buffer as processing/extraction media favoured the extraction process compared to the NaCl solution. Proteins extraction was significantly assisted by pressure. Equal/higher intensity than 400 MPa led to lower C-phycocyanin extraction yields, probably due to denaturation of proteins. High pressure conditions at 300 MPa for 10 min -using deionized water or phosphate buffer as medium- were selected as optimum, leading to higher extraction yields and purity extracts within ~2 h after processing. Highlights: C-phycocyanin and total soluble proteins extraction was enhanced by high pressure. Deionized water or phosphate buffer 0.1 M, pH: 6.8 selected as extraction media. Denaturation occurred for treatment higher than 400 MPa; lower C-phycocyanin yield. Selected HP conditions: 300 MPa, 10 min, 20 °C, for 90% C-pc extraction within ~2 h.